Transient lymphopenia in acutely unwell young infants. Issue 3 (1st March 2002) - Adamski, J K; Arkwright, P D; Will, A M; Patel, L
Abstract : The clinical outcome of 42 acutely unwell infants <3 months old with lymphopenia was retrospectively compared with that of 42 controls. Lymphopenic infants were significantly more likely to require active resuscitation and intensive care, independent of total leucocyte count, gender, degree of prematurity, and diagnosis.